Metacognitions in Patients With Frequent Mental Disorders After Diagnosis of Pulmonary Arterial Hypertension - Caldarone, Flora; Gebhardt, Philippa; Hoeper, Marius M.; Olsson, Karen M.; Fuge, Jan; Park, Da-Hee; Meltendorf, Tanja; Kamp, Jan C.; Stapel, Britta; Richter, Manuel J.; Gall, Henning; Ghofrani, Hossein A.; et al. (Frontiers in Psychiatry, 2022)
Background: The prevalence of mental disorders, particularly adjustment disorder (AD), major depressive disorder (MDD) and panic disorder (PD) is increased in patients with pulmonary arterial hypertension (PAH). However, it is unclear which pathogenic mechanisms determine their development and could therefore be targeted in prevention or therapeutic interventions. Here, we assessed metacognitions in a sample of PAH patients with and without MDD and PD. Moreover, we reconstructed the course of mental illnesses following the PAH diagnosis. Methods: 217 PAH patients were included in this cross-sectional study. The prevalence of AD was assessed retrospectively using DSM-V criteria. Current mental disorders were assessed using the structured clinical interview for DSM-V. Additionally, metacognitive beliefs and processes were assessed using established questionnaires (MCQ-30, AnTI). Results: Patients with an AD consecutive to the PAH diagnosis more frequently developed MDD (37.5% vs. 13.9%, p < .001) and PD (26.3% vs. 8.8%, p = .001) later on compared to PAH patients without a former AD. Moreover, patients with current MDD/PD displayed more dysfunctional metacognitions than those without current MDD/PD (p < .001). Patients with current MDD/PD in the context of former AD had more dysfunctional metacognitive worries and beliefs compared to patients with current MDD/PD without former AD (p = .009). Conclusion: Our results suggest that in the context of PAH, dysfunctional metacognitions are associated with MDD and PD. Therefore, a metacognitive approach to treat and prevent those mental illnesses seems promising and should be investigated in future studies.